Kynurenic Acid Analog Attenuates the Production of Tumor Necrosis Factor-α, Calgranulins (S100A 8/9 and S100A 12), and the Secretion of HNP1–3 and Stimulates the Production of Tumor Necrosis Factor-Stimulated Gene-6 in Whole Blood Cultures of Patients With Rheumatoid Arthritis - Balog, Attila; Varga, Borisz; Fülöp, Ferenc; Lantos, Ildikó; Toldi, Gergely; Vécsei, László; Mándi, Yvette (Frontiers in Immunology, 2021)
Objectives: Rheumatoid arthritis (RA) is a chronic, inflammatory joint disease with complex pathogenesis involving a variety of immunological events. Recently, it has been suggested that kynurenic acid (KYNA) might be a potential regulator of inflammatory processes in arthritis. KYNA has a definitive anti-inflammatory and immunosuppressive function. The aim of the present study is to investigate the complex effects of a newly synthesized KYNA analog—SZR72 on the in vitro production of tumor necrosis factor-α (TNF-α), tumor necrosis factor-stimulated gene-6 (TSG-6), calprotectin (SA1008/9), SA100 12 (EN-RAGE), and HNP1–3 (defensin-α) in the peripheral blood of patients with RA and the various effects of the disease. Methods: Patients with RA (n = 93) were selected based on the DAS28 score, medication, and their rheumatoid factor (RF) status, respectively. Peripheral blood samples from 93 patients with RA and 50 controls were obtained, and activated by heat-inactivated S. aureus. Parallel samples were pretreated before the activation with the KYNA analog N-(2-N, N-dimethylaminoethyl)-4-oxo-1H-quinoline-2-carboxamide hydrochloride. Following the incubation period (18 h), the supernatants were tested for TNF-α, TSG-6, calprotectin, S100A12, and HNP1–3 content by ELISA. Results: SZR72 inhibited the production of the following inflammatory mediators: TNF-α, calprotectin, S100A12, and HNP1–3 in whole blood cultures. This effect was observed in each group of patients in various phases of the disease. The basic (control) levels of these mediators were higher in the blood of patients than in healthy donors. In contrast, lower TSG-6 levels were detected in patients with RA compared to healthy controls. In addition, the KYNA analog exerted a stimulatory effect on the TSG-6 production ex vivo in human whole blood cultures of patients with RA in various phases of the disease. Conclusion: These data further support the immunomodulatory role of KYNA in RA resulting in anti-inflammatory effects and draw the attention to the importance of the synthesis of the KYNA analog, which might have a future therapeutic potential.